Social Construction of Disease and Stigma in Society: Analysis of Social Determinants of Health, Medical Service Accessibility, and Discrimination Against Chronic Disease Patients Through a Medical Sociology Perspective (International Journal of Economics Management and Social Science, 2026)
Background: Chronic diseases remain a major global health burden, yet their social dimensions—particularly stigma, discrimination, and unequal access to medical services—are often underexplored in mainstream health discourse. The social construction of illness shapes how patients are perceived and treated within communities and healthcare institutions alike. Objective: This study aims to analyze the social determinants of health, accessibility of medical services, and forms of discrimination experienced by chronic disease patients through a medical sociology perspective. Methods: A systematic literature review approach was adopted, drawing on peer-reviewed journal articles, policy reports, and sociological analyses published between 2019 and 2025. Sources were identified through databases including Scopus, Web of Science, and PubMed using keywords such as social stigma, chronic disease, medical sociology, social determinants, and healthcare discrimination. Results: Findings reveal that stigma construction is mediated by socioeconomic status, education, race, and geographic location. Chronic disease patients—particularly those with HIV/AIDS, tuberculosis, mental illness, and diabetes—face compounded stigma that impedes their willingness to seek care. Structural barriers further limit healthcare accessibility, disproportionately affecting marginalized groups. Conclusion: Medical sociology provides a critical lens for understanding how social forces construct illness identities and perpetuate discrimination. Intersectional and structural approaches are essential to address stigma and promote equitable healthcare access for chronic disease patients.Keywords: chronic disease, social determinants of health, medical sociology, stigma, healthcare discrimination, social construction of illness